The Principal and Quality Culture at SMP Negeri 3 Kotabaru: Implementation of Data-Based Curriculum Evaluation and Reflection - Assyakhirah Nur Ridha; Muhammad Hafiudin Rizaldi; Yeslin Anjelina Terayanti; Aslamiah Aslamiah; Celia Cinantya (Journal of Educational Sciences, 2026)
This study examines the principal’s leadership role in developing a quality culture through data-driven curriculum evaluation and reflective academic supervision at SMP Negeri 3 Kotabaru. Using a qualitative case study design, the research explores leadership practices, school quality culture, and the mechanisms used to evaluate the curriculum. Data were collected through in-depth interviews, participatory observations, and document analysis, then analyzed using Miles and Huberman’s framework of data reduction, data display, and conclusion drawing. The findings show that the principal functions as an instructional and transformational leader who combines managerial competence, professional guidance, and teacher empowerment through continuous reflection. The integration of data-driven approaches using the Education Report, the Computer-Based National Assessment (ANBK), and Sulingjar instruments supports more objective decision-making to meet student needs and enhance teacher performance. Collaborative and reflective academic supervision further strengthens a culture of continuous improvement within the school. Challenges such as limited teacher data literacy and restricted time for reflection are addressed through targeted training, mentoring, and the reinforcement of collective learning practices. Overall, the leadership model implemented at SMP Negeri 3 Kotabaru serves as an effective example of adaptive, participatory, and sustainable curriculum management aligned with the principles of the Merdeka Curriculum.